Primary scrotal lipoma in a child: a rare case report and review of literature - Kong, Meng; Bai, Yuexia; Jia, Jinhua; Liu, Chuanyang; Zhang, Shisong (Frontiers in Pediatrics, 2024)
Lipoma was a common benign tumor of the body surface, while scrotal lipoma was relatively rare. We reported a case of scrotal lipoma in a 5-year-old boy, which presented as a progressively enlarging scrotal mass. Scrotal ultrasonography highly suggested lipoma, and a scrotal mass resection was performed, with the final pathological diagnosis of benign scrotal lipoma.